Adaptation of the Serious Illness Conversation Guide to Singapore's Multicultural Setting for Patients With Heart Failure, Renal Failure, or Cancer - Anna So Youn Lee; Swee Noi Tang; Gillian Li Gek Phua; Alethea Chung-Pheng Yee; Shirlyn Hui-Shan Neo (Palliative Medicine Reports, 2024)
Background: The Serious Illness Conversation Guide (SICG) was developed by Ariadne Labs in the United States. However, there is a scarcity of literature on the cross-cultural adaptations of the SICG in Asian settings. Objectives: We aimed to adapt the SICG for English-speaking patients with serious illnesses in Singapore. Methods: We purposively recruited 28 patients with advanced stages of heart failure, renal failure, or cancer from a tertiary hospital. A designated research team member conducted semistructured interviews to obtain participants' feedback on the SICG. The interviews were transcribed by the designated study team member. Participants' response to each item on the SICG was coded quantitatively into categories to denote participant acceptance, partial acceptance, or nonacceptance. Transcripts were further analyzed using content analysis to understand participants' rationale regarding feedback of the specific SICG item. Modifications to the SICG were iteratively made over time to obtain its current version. Results: Participants indicated a preference for direct language with shorter sentences and inclusive pronouns. It was considered important that clinicians keep the conversation hopeful, individualize the conversation content according to the patient's journey, and use prompts where necessary to support the patient's elaboration. Conclusion: This study outlined a patient-centric approach to localizing the SICG in the English language to a new cultural context, marking the first such effort in an Asian setting. Further study is under way to evaluate the SICG in more disease populations and non-English languages used in Singapore.